ERNEST HEMINGWAY’S "A ROOM ON THE GARDEN SIDE": A LEXICAL-SEMANTIC STUDY OF THE GARDEN AGORONYM - Hikmatova Nigina Akmalovna (Research Focus International Scientific Journal, 2025)
The garden agoronym’s lexical-semantic importance in Ernest Hemingway’s short story A Room on the Garden Side is examined in this article. The term “agoronym”, which refers to place names that are connected to public or semi-public locations, is examined within the framework of the narrative to reveal its symbolic and thematic meanings. Through analyzing the semantic fields, connotations, and intertextual allusions associated with the term “garden”, the study explores the ways in which Hemingway utilizes spatial lexemes to create meaning, arouse sentimentality, and strengthen existential themes. The approach emphasizes the ways in which Hemingway’s portrayals of struggle, exile, and fleeting beauty interact with physical space and psychological moods while taking historical, cultural, and linguistic considerations into consideration.